1997
DOI: 10.1074/jbc.272.31.19601
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Bradykinin Receptor Ligand Binding Affinity and Its Coupled G-proteins by Nitric Oxide

Abstract: To determine whether nitric oxide (NO) can modulate bradykinin (BK) signaling pathways, we treated endothelial cells with an NO donor, S-nitrosoglutathione (GSNO), to determine its effect(s) on G-proteins (G i and G q ) that are coupled to the type II kinin (BK 2 ) receptor. Radioligand binding assays and Western analyses showed that GSNO (10 -500 M, 0 -72 h) did not alter the expression of BK 2 receptor, G i , or G q . However, GSNO caused a 6-fold increase in basal cGMP production and decreased high affinity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 36 publications
(44 reference statements)
2
43
0
1
Order By: Relevance
“…However, it was within the range reported for cultured airway epithelial cells (29). The number of binding sites/cell (B max ) was approximately equal to that which has been reported for bovine aortic endothelium (24).…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…However, it was within the range reported for cultured airway epithelial cells (29). The number of binding sites/cell (B max ) was approximately equal to that which has been reported for bovine aortic endothelium (24).…”
Section: Discussionsupporting
confidence: 49%
“…Our study of B 2 receptor binding characteristics confirmed the presence of B 2 receptors and demonstrated similar numbers of binding sites and bradykinin binding affinity in the two bronchial endothelial cell types. These receptors demonstrated a somewhat lower binding affinity (K d ϭ 5-6 nM) compared with that reported for bovine systemic and pulmonary endothelium (K d ϭ 0.5-2.0 nM) (24). However, it was within the range reported for cultured airway epithelial cells (29).…”
Section: Discussionmentioning
confidence: 42%
“…(2). S-nitrosothiols also decreased coupling of M 2 muscarinic, bradykinin, and AT 1 GPCR to their respective G proteins (5, 7) (22). NO does have other effects on GPCR signaling, including desensitization.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported effects of NO on signaling through the ␤ 2 -adrenergic receptors, as well as bradykinin, M 2 muscarinic, thromboxane, and AT 1 GPCRs. (2,5,22,31,32). The effects of NO on these GPCR-mediated responses have both cGMP-dependent and -independent components that, together with our data on the 5-HT GPCR system (23), raise the issue of cGMP-independent regulation of GPCRs by S-nitrosothiols as a general physiological mechanism for the regulation of vascular signal transduction.…”
mentioning
confidence: 88%
“…27 In addition, in endothelial cells, NO has been shown to selectively inhibit G proteins of the G i and G q family but not those of the G s family, and that this modulation of G proteins could have a permissive action on the G s -AC pathway. 28 Therefore, it is possible that NO can activate AC via the potential modulation of G protein.…”
Section: Involvement Of Cgmp and Campmentioning
confidence: 99%